Modeling of finite deformation process in anisotropic bodies - Khristich, Dmitriy Viktorovich (Computational Continuum Mechanics, 2013)
The behavior of an anisotropic medium at finite deformations under external forces in the inhomogeneous non-stationary external temperature field with account of the mutual influence of deformation and temperature fields is considered. Coupled equations of equilibrium and heat conductivity in the variational form are obtained. The closed system of equations for solving the coupled thermoelasticity problem is presented. The stress-strain state of a multilayer cylinder made of a composite material is investigated. The cylinder is subject to an internal pressure in the inhomogeneous temperature field generated by the external heat sources. It is shown that the number of composite layers and the orientation of main anisotropy axes in each layer have a significant effect on the axial and tangential stresses arising between layers.